Database Systems: A Practical Approach to Design, Implementation and Management - Thomas Connolly (Pearson Education, 2008)
This Book places a strong emphasis on good design practice, allowing students to master design Methodology in an accessible, step-by-step fashion. A Clear introduction to design implementation and Management issues, as well as an extensive treatment of database languages and standards, make this book an indispensable complete reference for database students and professionals. The book is designed to be used in database courses for technical and non-technical students.